The Marmoset as an Animal Model of Influenza: Infection With A(H1N1)pdm09 and Highly Pathogenic A(H5N1) Viruses via the Conventional or Tracheal Spray Route - Iwatsuki-Horimoto, Kiyoko; Nakajima, Noriko; Kiso, Maki; Takahashi, Kenta; Ito, Mutsumi; Inoue, Takashi; Horiuchi, Machiko; Okahara, Norio; Sasaki, Erika; Hasegawa, Hideki; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2018)
To control infectious diseases in humans, it is important to understand the pathogenicity of the infecting organism(s). Although nonhuman primates, such as cynomolgus and rhesus macaques, have been used for influenza virus infection models, their size can limit their use in confined animal facilities. In this study, we investigated the susceptibility of marmosets to influenza viruses to assess the possibility of using these animals as a nonhuman primate model for influenza research. We first used an influenza A (H1N1)pdm09 virus to compare two inoculation routes: the conventional route, via a combination of the intratracheal, intranasal, ocular, and oral routes; and the tracheal spray route. In marmosets inoculated via the tracheal spray route, we found inflammation throughout the lungs and trachea. In contrast, in marmosets inoculated via the conventional route, the inflammation was confined to roughly the center of the lung. These data suggest that the tracheal spray route may be more suitable than the conventional route to inoculate marmosets with influenza viruses. We also tested an influenza A(H5N1) highly pathogenic avian influenza (HPAI) virus and found that some marmosets inoculated with this virus via the tracheal spray route showed weight loss, decreased body temperature, and loss of appetite and activity. The replication of this H5N1 virus in respiratory organs was confirmed. These results indicate the potential of marmosets as an animal model for infection with seasonal or HPAI viruses.